2005
DOI: 10.1111/j.1467-9515.2005.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Housing and Accommodation of Irish Travellers: From Assimilationism to Multiculturalism and Back Again

Abstract: This article charts the changing conceptualization of Travellers in relevant Irish central government policy statements since the   s, together with the accommodation policy initiatives devised on this basis. It interprets developments in this regard as a movement from assimilationism to integrationism to (weak) multiculturalism. The article also reveals a significant "policy implementation deficit", which is manifested in two ways. Firstly, accommodation output has generally failed to meet central governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The experience of these committees varies across the country but they have not delivered what many Travellers wanted. Traveller NGOs have published very critical reports on the process (Irish Traveller Movement 2001;Cronin 2003), and this is confirmed by academic analysis (Norris and Winston 2005). 13 The publication of the 2000 Report of the National Traveller Accommodation Consultative Committee confirmed that progress had been very slow (National Traveller Accommodation Consultative Committee 2000a), while an official evaluation of the consultative committees reported that Traveller participants were more likely than others to be unhappy about the procedures (National Traveller Accommodation Consultative Committee 2000b).…”
Section: Statutory Duty To Consult: Accommodationmentioning
confidence: 92%
See 1 more Smart Citation
“…The experience of these committees varies across the country but they have not delivered what many Travellers wanted. Traveller NGOs have published very critical reports on the process (Irish Traveller Movement 2001;Cronin 2003), and this is confirmed by academic analysis (Norris and Winston 2005). 13 The publication of the 2000 Report of the National Traveller Accommodation Consultative Committee confirmed that progress had been very slow (National Traveller Accommodation Consultative Committee 2000a), while an official evaluation of the consultative committees reported that Traveller participants were more likely than others to be unhappy about the procedures (National Traveller Accommodation Consultative Committee 2000b).…”
Section: Statutory Duty To Consult: Accommodationmentioning
confidence: 92%
“…The national committee chairperson was stern, saying that the failure to provide basic accommodation for 1,000 families in a time of economic prosperity was unacceptable (Healy 2000). Academic commentators have identified a range of factors impeding progress on this issue, with public opinion, local administration practices and the decisions of local and national politicians being important impediments (Norris and Winston 2005).…”
Section: Statutory Duty To Consult: Accommodationmentioning
confidence: 99%
“…Each of these planning jurisdictions has a complex body of planning law, case law, policy and circulars that illustrate state responses to the provision of Traveller-Gypsy accommodation, whose intricacies are not being explored here. The situation in the Republic of Ireland has followed a similar trajectory, despite the higher visibility of Irish Travellers (Norris & Winston, 2005). 10.…”
Section: Geraint Ellis and Catharine Mcwhirtermentioning
confidence: 93%
“…But in practice this 'impartiality' is inflected by the imaginaries of the ethnic nation which privilege the majority culture and restrict meaningful public space for ethnic difference (Hall 2000). Though no longer overtly assimilationist, government policy responses to the so-called Irish Traveller 'problem' have progressively made it impossible, and ultimately illegal, to maintain the nomadic lifestyle around a circuit of traditional stopping points that is at the heart of Traveller culture (Crowley 2005;Helleiner 2000;Mulcahy 2011;Norris and Winston 2005;Fanning 2002;. Efforts to empower Travellers through a model of active citizenship and democratic participation, promote respect for Traveller culture, and 'accommodating' Traveller mobility through the provision of transient sites since the late 1990s, have been severely compromised by local authority failure to provide sites and by legislation that further criminalized traveller mobility (Crowley and Kitchin 2007).…”
Section: Technologies Of Recognitionmentioning
confidence: 99%